Knowledge transfer of the wireless healthcare application in rural community: A case study in Baling, Kedah - Mahmuddin, Massudi; Ahmad, Mazida; Bakar, Rosmadi; Md Rejab, Mawarny; Che Pa, Noraziah; Baharin, Ahmad Tajudin (2012)
Healthcare system in rural area is equally as important as who live in the urban or modern city counterparts.Due to geographically difficulty to access by the modern transportation, wireless communication is one of the possible approaches to reach these areas.On the key aspect is the infrastructure reliability to securing knowledge transfer amongst knowledge of the rural society.This study is to determine the readiness of the rural communities in accepting wireless healthcare applications for the effective transfer of acquired knowledge from healthcare expertise to the rural communities.The instruments were developed and survey was conducted in rural area of Baling, Kedah. 435 questionnaires have been distributed and only 245 are qualified to be analyzed using quantitative analysis.The result shows that the rural communities are appreciate and long-wait with this new type of technology in helping them to improve the healthcare rural system even though the wireless infrastructure is hindering.